Ultrasonic-Assisted Extraction of Polysaccharides from Schizochytrium limacinum Meal Using Eutectic Solvents: Structural Characterization and Antioxidant Activity - Xinyu Li; Jiaxian Wang; Guangrong Huang; Zhenbao Jia; Manjun Xu; Wenwei Chen (Foods)
To address the underutilization of Schizochytrium limacinum meal, polysaccharides from Schizochytrium limacinum meal (SLMPs) were prepared via ultrasonic-assisted eutectic-solvent-based extraction. Although polysaccharides exhibit promising application potential, the structural ambiguity of SLMPs necessitates systematic investigation to elucidate their structure–activity relationships, thereby providing a scientific foundation for their subsequent development and utilization. Using response-surface methodology (RSM), the optimized extraction conditions were determined as follows: ultrasonic temperature of 52 °C, ultrasonic duration of 31 min, ultrasonic power of 57 W, water content of 29%, and a material-to-liquid ratio of 1:36 g/mL. Under these conditions, the maximum polysaccharide yield reached 9.25%, demonstrating a significant advantage over the conventional water extraction method (4.18% yield). Following purification, the antioxidant activity and structural characteristics of SLMPs were analyzed. The molecular weight, monosaccharide composition, reducing groups, and higher-order conformation were systematically correlated with antioxidant activity. Fourier-transform infrared spectroscopy (FTIR), monosaccharide composition analysis, and 1H nuclear magnetic resonance (NMR) spectroscopy revealed characteristic polysaccharide functional groups (C–O, O–H, and C=O). Monosaccharides such as glucose (Glc), galactose (Gal), and arabinose (Ara) were found to enhance antioxidant activity. High-performance gel permeation chromatography (HPGPC) indicated a molecular weight of 20.7 kDa for SLMPs, with low-molecular-weight fractions exhibiting superior antioxidant activity. Scanning electron microscopy (SEM) further demonstrated that ultrasonically extracted polysaccharides possess porous structures capable of chelating redox-active functional groups. These findings suggest that ultrasonic-assisted eutectic-solvent-based extraction is an efficient method for polysaccharide extraction while preserving antioxidant properties.